Role of endoscopic ultrasonography in staging of esophageal carnicoma - Uğur YILMAZ,; Ahmet TEZEL,; Ülkü SARITAŞ,; Bülent YILDIRIM,; Senem KÜÇÜKBAŞ,; Gülay TEMUÇİN, (Turkish Journal of Gastroenterology, 2020)
-